Penerapan Manajemen Waktu Pada Proyek Pembangunan Stasiun Kereta Api Lintas Makassar-Parepare dengan Menggunakan Metode CPM - Rona Emilia Panggeso; Josefine E Latupeirissa; Herby Calvin P Tiyouw (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
CPM (Critical Path Method) is one of the most advanced network planning methods that leads to project timing decisions, and time estimation is deterministic/clear. The purpose of research using this method is to determine the time and cost of scraping and to find out which activity is one of the key activities. It also aims to control and coordinate various activities to get projects completed in the right time frame, helping companies plan and control projects in a more time- and cost-effective manner. The research was conducted by processing data obtained from observations in the field, interviews with project employees and also secondary data in the form of project time schedules. With the use of this CPM method, it produces three critical paths with 27 series of activities, 19 of which are critical and the remaining 8 are non-critical. The calculation results using the CPM method took 626 days with 207 days of non-critical activities. Based on the CPM method, it is necessary to reduce the workforce in non-critical activities by 8 workers and 15 workers. The labor reduction reduces slack and minimizes the labor costs of the project.